1998
DOI: 10.4319/lo.1998.43.1.0065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbohydrate production by the diatom Nitzschia curvilineata on the erodibility of sediment

Abstract: The effect of growth and carbohydrate production by the diatom Nitzschia cuwilineata on sediment erodibility was explored in laboratory flume experiments. Diatom cultures, incubated on sediment, were monitored daily for chlorophyll and carbohydrate concentrations and eroded in a recirculating flume at successive stages of growth. Because variations in erosion rate were far greater than variations in erosion threshold during the diatom growth period, erosion rate may be a more sensitive index of sediment stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(114 citation statements)
references
References 36 publications
8
103
1
2
Order By: Relevance
“…Microphytobenthos can increase sediment stability (Madsen et al 1993) through the alteration of adhesive-cohesive bonding among particles, thereby reducing sediment erodibility. However, the age of the microphytobenthos mat can also affect the critical erosional velocities (Madsen et al 1993, Sutherland et al 1998. We observed oxygen bubbles in the mat that may have lifted the carpet, facilitating microphytobenthos erosion and leading to mass erosion at a moderate bottom shear of about 0.6 cm s -1 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Microphytobenthos can increase sediment stability (Madsen et al 1993) through the alteration of adhesive-cohesive bonding among particles, thereby reducing sediment erodibility. However, the age of the microphytobenthos mat can also affect the critical erosional velocities (Madsen et al 1993, Sutherland et al 1998. We observed oxygen bubbles in the mat that may have lifted the carpet, facilitating microphytobenthos erosion and leading to mass erosion at a moderate bottom shear of about 0.6 cm s -1 .…”
Section: Discussionmentioning
confidence: 85%
“…Water flow can alter the direction and magnitude of process pathways and affect benthic-pelagic coupling. bottom shear velocity (shear stress) affects diffusional processes at the sediment -water interface (Dade 1993, Sanford & Crawford 2000, sediment erosion (Maa et al 1993), microphytobenthos erosion (Madsen et al 1993, Yallop et al 1994, Sutherland et al 1998, and possibly nutrient transformations and regeneration (Boynton 1985, Santschi et al 1990). Benthic suspensions feeders and flow interact in many ways (Wildish & Kristmanson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Benthic algae produce extracellular polymeric substances (EPS, mainly colloidal carbohydrates), which increase the cohesiveness of the sediments, and this is reflected in the significant relationship between U crit (and mass eroded) and the chlorophyll a content of surface sediments (r = 0.54; p = 0.005 for 1996 and 1997 data). Field studies (Sutherland et al 1998b, Austen et al 1999, Paterson et al 2000, Widdows et al 2000a) have consistently demonstrated a significant correlation between sediment stability and the content of chlorophyll a and EPS in the surface sediments. Furthermore, controlled laboratory flume experiments have confirmed that there is a cause-effect relationship between microphytobenthos chlorophyll a (and EPS) and sediment stability (Sutherland et al 1998a).…”
Section: Spatial and Temporal Changes In Sediment Resuspension And Dementioning
confidence: 99%
“…In the intertidal zone, sediment stability is increased by organisms like microphytobenthos that cause adhesion of grains (e.g. Sutherland et al 1998) and decreased by bioturbators such as deposit-feeding bivalves (e.g. Macoma balthica) and grazers (e.g.…”
Section: Introductionmentioning
confidence: 99%